2010
DOI: 10.1007/s00203-010-0546-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the equol-producing bacterium Slackia sp. strain NATTS

Abstract: Several kinds of carbohydrates such as sorbose, adonitol, and melezitose were found to enhance equol production from daidzein in an in vitro human fecal culture. Sorbose, one of the most effective carbohydrates, was used as a carbohydrate source for isolating the NATTS strain, which was a Gram-positive, non-spore-forming rod bacterium with high ability to convert daidzein to equol isolated from the 7th maintenance culture. The strain was found to belong to the genus Slackia family Coriobacteriaceae by 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 37 publications
2
63
1
Order By: Relevance
“…In the present study, detection proportions of subjects for Slackia sp. strain NATTS in cases and controls were smaller than these percentages shown by Tsuji et al (2010).…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In the present study, detection proportions of subjects for Slackia sp. strain NATTS in cases and controls were smaller than these percentages shown by Tsuji et al (2010).…”
Section: Discussioncontrasting
confidence: 59%
“…strain NATTS have a potent equol-producing ability from daidzein. Tsuji et al (2010) reported that the detection rate of Slackia sp. strain NATTS in the feces of 40 healthy volunteers were 33% in subjects under 40 years old and were 47% in subjects over 40 years old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…strain NATTS, which has potent daidzein-to-equol conversion ability, from healthy human feces (26). This strain has a more potent daidzein-equol conversion activity than the other equol-producing strains previously reported (26).…”
mentioning
confidence: 87%